Pregnancy-induced changes in cell-fate in the mammary gland - Ginger, Melanie R (BioMed Central, 2003)
The protective effect of an early full-term pregnancy is a well established phenomenon; in contrast, the molecular and cell-specific mechanisms that govern parity-specific changes in the mammary gland have not been well described. Recent studies signify a dramatic advance in our understanding of this phenomenon, and indicate a 'cell fate' model for parity-related changes that lead to protection against breast cancer.